Effectiveness of sterilisation of oil palm bunch using microwave technology - Sukaribin, Nazarulhisyam; Khalid, Kaida (Elsevier, 2009)
The extraction of crude palm oil from oil palm bunches requires the bunch to be sterilised and the fruitlet detached before it can be further processed for oil recovery. Research was carried out to find ways to reduce oil loss in condensate and make sterilisation a continuous process. This paper discusses a laboratory scale study on microwave sterilisation, together with the microwave dielectric properties and moisture content surrounding the abscission layer of oil palm fruitlets. An interesting result was found where the moisture content was higher in the abscission region as compared to the other regions of the fruitlet. With stripping efficiency above 80%, we conclude that microwave radiation is suitable for quick detachment of the fruitlet from the bunch since the abscission layer is heated-up and fruit loosening performed without damaging other regions of the fruit.